LMNB1-Related Adult-Onset Autosomal Dominant Leukodystrophy Presenting as Movement Disorder: A Case Report and Review of the Literature - Zhang, Yanyan; Li, Jie; Bai, Rong; Wang, Jianping; Peng, Tao; Chen, Lijie; Wang, Jingtao; Liu, Yanru; Tian, Tian; Lu, Hong (Frontiers in Neuroscience, 2019)
Adult-onset autosomal dominant leucodystrophy (ADLD) is a lately described rare form of leukodystrophy with only one family report from China. As the only disease associated with lamina B1 encoded by LMNB1, ADLDs have different clinical presentations, ranging from autonomous to pyramidal tract and cerebellar ataxia. Here we are reporting a case of ADLD which presented with positional tremor as the initial symptom, and later, to progressive autonomanous and pyramidal signs and symptoms developed. T2-weighted brain MRI showed brain atrophy and diffuse high signal intensity of the cerebral white matter and the brain stem. The precise diagnosis was made by identification of the mutated gene. To the best of our knowledge, this is perhaps the first case report of ADLD presenting as tremor in China.